Peranan Penerapan HRIS dan Kepuasan Kerja Terhadap Kinerja Karyawan di PT Pisma Putra Textile - Hakim, Mujibul; Hidayat, Husni; Fanani, M. Rudi (Jurnal Manajemen, 2022)
The study tested the HRIS variable and job satisfaction on employee performance variables at PT Pisma Putra Textile. The study used a descriptive and qualitative approach, data processing using the SPSS application, data collection techniques using questionnaires, research instruments using a Likert scale and direct interviews with the Head of HRD, IT division, and operational employees of PT Pisma Putra Textile. Data analysis techniques through validity, reliability, and multiple regression analysis. Respondents were 125 employees. This study shows a significant relationship between the HRIS variable and the employee performance variable with a positive coefficient value of 0.333 and a significant relationship between the job satisfaction variable and the employee performance variable with a positive coefficient value of 0.324. In addition, there is a significant relationship between the HRIS variable and the job satisfaction variable on the employee performance variable with an F-count value of 31,395 and a significance value of 0.000. Thus, the conclusion of this study shows that the HRIS variable and job satisfaction can support improving employee performance, meaning that the first hypothesis (H1) and the second hypothesis (H2) are accepted. Performance can be measured by the results of the work being close to perfect, the results of the work according to the target, effective in completing the work and the work given by the leadership is carried out with full responsibility. While the results of interviews with HRD managers at PT Pisma Putra Textile, the ability of employees to work together with teams according to their respective main tasks in completing work on time can improve employee performance.